2021
DOI: 10.3390/ma14205968
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of the Mechanical and Durability Properties of High-Performance Concrete Materials for Grouting Underwater Foundations of Offshore Wind Turbines

Abstract: With the increasing importance of offshore wind turbines, a critical issue in their construction is the high-performance concrete (HPC) used for grouting underwater foundations, as such materials must be better able to withstand the extremes of the surrounding natural environment. This study produced and tested 12 concrete sample types by varying the water/binder ratio (0.28 and 0.30), the replacement ratios for fly ash (0%, 10%, and 20%) and silica fume (0% and 10%), as substitutes for cement, with ground gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The results of the complex modulus tests demonstrated that the optimized binder formulation, M2, consistently exhibited a higher complex modulus than M1 across all sweep frequencies, with an average value of 15.48 GPa. This nding indicates that M2 has a higher stiffness than M1, which could potentially improve the material's durability and resistance to pathological manifestations such as cracking (Kuo & Zhuang, 2021;Myrtja et al, 2021c).…”
Section: Splitting Tensile Strength Results Mortars Formulationsmentioning
confidence: 93%
See 2 more Smart Citations
“…The results of the complex modulus tests demonstrated that the optimized binder formulation, M2, consistently exhibited a higher complex modulus than M1 across all sweep frequencies, with an average value of 15.48 GPa. This nding indicates that M2 has a higher stiffness than M1, which could potentially improve the material's durability and resistance to pathological manifestations such as cracking (Kuo & Zhuang, 2021;Myrtja et al, 2021c).…”
Section: Splitting Tensile Strength Results Mortars Formulationsmentioning
confidence: 93%
“…As reported by literature, the use of silica fume (SF) in concrete can signi cantly enhance its compressive strength and elastic modulus, essential properties in those applications (Fattouh & Elsayed, 2023;Keerio et al, 2022;Boukhelf et al, 2021). Kuo & Zhuang (2021) also presented evaluations on high-performance concrete for aerogenerators foundations. It was found that a higher modulus of elasticity, compared to the usual values for normalstrength concrete, were more suitable for that application having an improved resistance to the mechanical and environmental loads incident from the aerogenerators' usual operation.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The particularity of grouting of offshore wind power lies in that the offshore fan is under the action of reciprocating random load, and the grouting connection section is under the combined action of axial force, bending moment, torque and other loads, which makes the grouting material work in a complex stress state. Different from traditional grouting materials, wind power grouting materials are required to have higher fluidity and higher stability in the pumping stage, and also to have high mechanical properties [11,12]. Currently, researchers have conducted extensive research on the fluidity, volume stability, and mechanical properties of grouting materials.…”
Section: Introductionmentioning
confidence: 99%
“…The imaginary part corresponds to the material's characteristic to dissipate energy, also called the loss modulus. It is important to note that despite being called the dynamic modulus, there are no inertial effects involved (Brinson & Brinson, 2008;Kuo & Zhuang, 2021;Saucedo et al, 2013b)…”
mentioning
confidence: 99%